Role of Employee Empowerment in Organizational Development (International Journal of Scientific Research and Management (IJSRM), 2016)
Organizations today understand that in a knowledge-driven economy, speed in taking decisions, efficient methods of functioning and innovative ideas help them gain an edge over competitors. This view point that organizations are adopting a strategy of employee empowerment. Employee empowerment is considered as an important issue in human resource management organizations and it is important that each of the individuals feel about their competence. Human resources consider as strategic asset of the organization and empowerment of employees, is a new approach in order to human resource development that cause increase productivity improve quality, and profitability of products and services of organizations. Sharing power with others will expand one’s own power. People who have higher opportunity for growth and mobility in their work are more likely to have high aspiration and to be more committed to the organization. This article explain the importance of empowerment in organizational development and also the role of management, employers and employees in organization development though empowerment.